História e aspectos do cotidiano da hospedaria de imigrantes do Cristal Porto Alegre (1890-1898) - Silva, Gabriela Ucoski da (2014)
The purpose of this paper is to question the organization, functioning and everyday life of the Immigrant`s Inn of Cristal District, space created to the reception of the new coming immigrant in Porto Alegre in the last decade of the XIX century. From this century on, a wide flow of people starts to leave their countries in search of a new life, especially in the three Americas. In front of this fact, innumerable politics intended to treat the immigration and the colonization were created, standing out the ones involved with the procedures adopted in the moment of the arrival of these population flow. Among them, there was the creation of the immigrant`s inn, institutions that became common in that period. Rio Grande do Sul, in its turn, obeying to the central government mandate, cared for providing such institutions, especially in Porto Alegre. Meanwhile, few studies deal with this subject. Furthermore, a great corpus documental of the Immigrant`s Inn of Cristal District made it possible to know how the immigrant`s accommodation happened in the moment that the immigration flow was intense, beyond the history of that institution. The study permitted, still, understand the Brazilian and Rio Grande do Sul immigration politician turned back to the reception and accommodation of the new comers, as well as changes, problems and difficulties faced alongside the time in that enterprise, singularly in Rio Grande do Sul.